Experience-dependent central vision deficits: Neurobiology and visual acuity. (September 2015) - Williams, Kate; Balsor, Justin L.; Beshara, Simon; Beston, Brett R.; Jones, David G.; Murphy, Kathryn M.
Highlights: MD causes greater acuity loss in the center of vision. The loss of vision affects deprived eye and binocular acuity. MD has regional effects on expression of AMPAR proteins in V1. MD causes persistent loss of AMPARs in the central region of V1. MD causes transient loss of AMPARs in the peripheral and monocular regions of V1. Abstract: Abnormal visual experience during childhood often leads to amblyopia, with strong links to binocular dysfunction that can include poor acuity in both eyes, especially in central vision. In animal models of amblyopia, the non-deprived eye is often considered normal and what limits binocular acuity. This leaves open the question whether monocular deprivation (MD) induces binocular dysfunction similar to what is found in amblyopia. In previous studies of MD cats, we found a loss of excitatory receptors restricted to the central visual field representation in visual cortex (V1), including both eyes' columns. This led us to ask two questions about the effects of MD: how quickly are receptors lost in V1? and is there an impact on binocular acuity? We found that just a few hours of MD caused a rapid loss of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor proteins across all of V1. But after a few days of MD, there was recovery in the visual periphery, leaving a loss of AMPA receptors only in the central region of V1. We reared animals with early MD followed by a long period of binocular vision and found binocular acuity deficits that were greatest in the central visual field. Our results suggest that the greater binocular acuity deficits in the central visual field are driven in part by the long-term loss of AMPA receptors in the central region of V1.